Recurrent Painful Ophthalmoplegic Neuropathy with Unilateral Oculomotor and Trochlear Nerve Palsy in an 8-year-old Girl. Issue 4 (2nd October 2022) - Akhondian, Javad; Ashrafzadeh, Farah; Seilanian Toosi, Farrokh; Esmaeilzadeh, Mahla; Beiraghi Toosi, Mehran; Imannezhad, Shima; Saeedi Zand, Nazanin; Hashemi, Narges
ABSTRACT: Background: Recurrent painful ophthalmoplegic neuropathy (RPON) is a rare disorder with a unilateral headache accompanied by ipsilateral episodes of painful ocular cranial nerve neuropathy, which typically occurs in childhood. Case report: We report an 8-year-old female with four episodes of RPON involving unilateral third and fourth cranial nerves. Right eye exotropia and complete ptosis were detected on examination. Brain MRI images revealed right third nerve enhancement where it exits from the brainstem. She completely recovered after 5 weeks with the administration of prednisolone and indomethacin. Discussion and conclusion: Due to the rarity of this condition in children, recurrent painful ophthalmoplegic neuropathy should be considered as a differential diagnosis of unilateral or bilateral painful ophthalmoplegia, particularly with a history of migrainous headache. Since it is a treatable entity, and repeated attacks may lead to permanent sequela, early intervention is crucial.